A smart viral vector for targeted delivery of hydrophobic drugs - Sukanya Ghosh (Nature Portfolio, 2021)
Abstract Targeted delivery of hydrophobic chemotherapeutic drugs to tumor cells remains a fundamental problem in cancer therapy. Effective encapsulation of hydrophobic drugs in nano-vehicles can improve their pharmacokinetics, bioavailability and prevent off-target localization. We have devised a method for easy chemical conjugation and multivalent display of a tumor-homing peptide to virus-like particles of a non-mammalian virus, Flock House Virus (FHV), to engineer it into a smart vehicle for targeted delivery of hydrophobic drugs. This conjugation method provides dual functionalization to the VLPs, first, a 2 kDa PEG spacer arm shields VLPs from immune reactivity, and second, attachment of the tumor homing peptide tLyP-1 chauffeurs the encapsulated hydrophobic drugs to target cells. The fortuitous affinity of the FHV capsid towards hydrophobic molecules, and dependence on Ca2+ for maintaining a stable capsid shell, were utilized for incorporation of hydrophobic drugs—doxorubicin and ellipticine—in tLyP-1 conjugated VLPs. The drug release profile from the VLP was observed to be gradual, and strictly endosomal pH dependent. We propose that this accessible platform empowers surface functionalization of VLP with numerous ligands containing terminal cysteines, for generating competent delivery vehicles, antigenic display and other biomedical applications.